Oral Microbial Determinants of Saliva and Serum Lipopolysaccharide Activity - Manzoor, M.; Putaala, J.; Zaric, S.; Leskelä, J.; Dong, A.; Könönen, E.; Lahti, L.; Paju, S.; Pussinen, P. J. (SAGE Publications, 2026)
Lipopolysaccharide (LPS) is a virulence factor of gram-negative bacteria, and endotoxemia or translocation of LPS in serum plays a significant role in oral and systemic pathologies. The contribution of the oral microbiome composition to saliva LPS activity and endotoxemia remains unclear. We investigated whether salivary and serum LPS levels are associated with oral microbiome diversity, taxonomic profiles, and functional characteristics. The oral microbiome was analyzed using metagenomic sequencing of saliva from 298 individuals enrolled in a multicenter case-control study, SECRETO (NCT01934725). Serum and salivary LPS activities were measured, and multiple linear regression models were fitted to identify the microbial taxa that predicted LPS levels. MaAsLin2 (Microbiome Multivariable Associations with Linear Models) was used to determine the associations of microbial functional features and LPS levels. Salivary alpha diversity was positively associated with serum LPS but negatively associated with salivary LPS, smoking, and antibiotic use in the preceding 1 to 6 mo. Community composition (beta diversity) differed between the salivary LPS tertiles (P = 0.001) but not between serum LPS tertiles. In total, 10 oral taxa associated with serum LPS tertiles and 59 with salivary LPS tertiles were identified. Prevotella, Neisseria, Leptotrichia, and Porphyromonas had significant positive associations with salivary LPS, whereas Fusobacterium had a negative association. Among these genera, Prevotella sp. E13_17, P. gingivalis, L. wadei, and F. nucleatum were the species with the strongest associations. Among the 1,016 oral microbiome metabolic features, several were linked to the biosynthesis of LPS, lipid A, and O-antigen pathways. The oral microbiome composition was strongly associated with salivary LPS activity in addition to weaker links to serum LPS. Oral microbiota–derived LPS activity in saliva was associated with microbial metabolism characterized by the predominance of proliferation and biosynthesis pathways. Our study indicates that dysbiosis of the oral microbiome is a source of increased salivary and serum LPS activity.